2013
DOI: 10.1515/bejeap-2013-0065
|View full text |Cite
|
Sign up to set email alerts
|

New Labour? The Effects of Migration from Central and Eastern Europe on Unemployment and Wages in the UK

Abstract: Abstract:The UK was one of only three countries that granted free movement of workers to accession nationals following the enlargement of the European Union in May 2004. The resulting migration inflow, which was substantially larger and faster than anticipated, arguably corresponds more closely to an exogenous supply shock than most migration shocks studied in the literature. We evaluate the impact of this migration inflow -one of the largest in British history -on the UK labour market. We use new monthly micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…At the same time, those in employment do not seem to be threatened by labour market competition, as their life satisfaction increases with the levels of local immigration. This is consistent with the evidence that the post-enlargement immigration did not have adverse effects on UK wages and unemployment (Gilpin et al, 2006;Lemos and Portes, 2013;Lemos, 2014), as well as the evidence that natives move to other, potentially more desirable, types of jobs (such as communication-intensive jobs) as immigrants come in (Peri, 2014). The negative association between the local immigration rate and life satisfaction among the economically inactive echoes the negative association between the two variables among the elderly: the latter are retired and less likely to 19 Unfortunately, the BHPS does not contain information on individual attitudes towards immigration and we are unable to test whether the negative relationship between age and pro-immigration attitudes holds in our case.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…At the same time, those in employment do not seem to be threatened by labour market competition, as their life satisfaction increases with the levels of local immigration. This is consistent with the evidence that the post-enlargement immigration did not have adverse effects on UK wages and unemployment (Gilpin et al, 2006;Lemos and Portes, 2013;Lemos, 2014), as well as the evidence that natives move to other, potentially more desirable, types of jobs (such as communication-intensive jobs) as immigrants come in (Peri, 2014). The negative association between the local immigration rate and life satisfaction among the economically inactive echoes the negative association between the two variables among the elderly: the latter are retired and less likely to 19 Unfortunately, the BHPS does not contain information on individual attitudes towards immigration and we are unable to test whether the negative relationship between age and pro-immigration attitudes holds in our case.…”
Section: Discussionsupporting
confidence: 91%
“…Following the 2004 enlargement of the European Union, the UK opened its labor market to citizens of the new EU member states (Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Slovakia and Slovenia -also known as the accession or A8 countries). The resulting migrant inflow was the "biggest peacetime movement [ It has been shown that this unexpectedly large inflow of A8 migrants had no adverse effect on either UK wages or unemployment (Gilpin et al, 2006;Lemos and Portes, 2013;Lemos, 2014). 3 However, it has also been claimed that A8 immigrants have disadvantaged the UK's low-skilled and young workers (Sumption and Somerville, 2010;MigrationWatch, 2012), strained the provision of local public services 4 as well as been subject to exploitation and unfair treatment (Jayaweera and Anderson, 2008;BBC, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Migrant employees' location options are mainly determined by clusters and not by specifically advantageous labor market circumstances. Low-skilled residents are rather region-bound [13].…”
Section: The Labor Market Effects Of Immigrationmentioning
confidence: 99%
“…A large part of the debate on migration to the UK over the last decade has centered on the decision to provide unrestricted access to UK labor markets to nationals of the new EU member states immediately after accession (Dustmann and Frattini 2014;Lemos and Portes 2013). Migrants from new EU member states in the UK come mostly for work reasons and have higher employment rates than Old EU and British nationals (Clark and Drinkwater 2014;Drinkwater and Robinson 2013).…”
Section: Data and Definitionsmentioning
confidence: 99%